Assessment of Morpho-physiological Traits and Grain Yield of Corn (Zea mays L.) with Weed Interference - Ghorban didehbaz moghanlo; Ahmad Tobeh; hamid reza mohammaddoust; Sajjad Moharramnejad; Farid Ghol Zardie (Journal of Agricultural Science and Sustainable Production, 2022)
Background and Objective: In order to study of morpho-physiological attributes in corn under influence of weed, an experiment based on randomized complete block design with four replications was performed at the Moghan climate during 2020 growing season.Methods and Materials: The experiment was included 14 treatments; seven weed-infested and seven weed free treatments were applied at regular intervals as 0, 10, 20, 30, 40, 50 and 60 days after corn emergence in which weeds were allowed to grow until harvest, and weeds were removed, respectively. Total dry weight of weeds, plant height, length of ear, total biomass, leaf area index (LAI), crop growth rate (CGR), relative growth rate (RGR), net assimilation rate (NAR), leaf area duration (LAD), and yield of corn were measured.Results: The results showed that all measured traits were affected by weed interference duration and weed control period. Weed interference duration increased total dry weight of weeds and weed-free duration reduced total dry weight of weeds. Also, increase in weeds interference duration significantly reduced, plant height, length of ear, total biomass, LAI CGR, RGR, NAR, LAD, and grain yield of corn. On the other hand, total biomass, LAI, CGR, RGR, NAR, LAD, and grain of corn increased by rising weed-free duration.Conclusion: The weed interference duration had a significant effect on the final yield of corn and with interference of the all weed season, grain yield of corn decreased. Weed interference duration increased total dry weight of weeds and weed-free duration reduced total dry weight of weeds.